2020
DOI: 10.1029/2020gl088055
|View full text |Cite
|
Sign up to set email alerts
|

High Supersaturation in the Wake of Falling Hydrometeors: Implications for Cloud Invigoration and Ice Nucleation

Abstract: Aerosol particles, cloud droplets, and ice crystals, coupled through the supersaturation field, play an important role in the buoyancy and life cycle of convective clouds. This letter reports laboratory observations of copious cloud droplets and ice crystals formed in the wake of a warm, falling water drop, which is a laboratory surrogate for a relatively warm hydrometeor in atmospheric clouds, such as a graupel particle in the wet growth regime. Aerosols were activated in the regions of very high supersaturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…where D is the droplet diameter, and G( T ) is the rate of ice growth at water supercooling T . The growth rate G( T ) was studied by many research groups (e.g., Lindenmeyer et al, 1959;Hallett, 1964;Pruppacher, 1967a;Feuillebois et al, 1995;Shibkov et al, 2003Shibkov et al, , 2005and others). It was found that the velocity of ice growth along the c axis, G c , is considerably smaller than that along the a axis, G a (e.g., Macklin…”
Section: Droplet Freezing Timementioning
confidence: 99%
“…where D is the droplet diameter, and G( T ) is the rate of ice growth at water supercooling T . The growth rate G( T ) was studied by many research groups (e.g., Lindenmeyer et al, 1959;Hallett, 1964;Pruppacher, 1967a;Feuillebois et al, 1995;Shibkov et al, 2003Shibkov et al, , 2005and others). It was found that the velocity of ice growth along the c axis, G c , is considerably smaller than that along the a axis, G a (e.g., Macklin…”
Section: Droplet Freezing Timementioning
confidence: 99%
“…In the case of a liquid hydrometeor of density 10 3 kg m −3 , these Re corresponds to hydrometeors with diameter between 3 × 10 −4 m and 1.03 × 10 −3 m falling with terminal velocities between 1.21 and 4.03 m s −1 . The ambient relative humidity RH ∞ is varied from nearly saturated ( RH ∞ ∼ 100 % ) within the cloud (Siebert & Shaw, 2017) to a highly subsaturated condition in the open atmosphere (see also Prabhakaran et al, 2020). The supersaturation S=RH1=ρvfalse/ρvsfalse(Tfalse)1 is computed with respect to the water phase when T > 0°C and with respect to the ice phase when T ≤ 0°C by using the following empirical Equations and for liquid and frozen hydrometeors, respectively (Huang, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Physical processes contributing to the production of secondary ice particles (Field et al, 2017) within a mature cloud cannot explain the observed discrepancies between the measured activation and the observed hydrometeor population, which is several orders of magnitude higher than expected (Huang et al, 2017; Pruppacher & Klett, 2010). One possible explanation of this riddle might be the wake‐induced supersaturation (Chouippe et al, 2019; Fukuta & Lee, 1986; Gagin, 1972) and activation of aerosols behind large precipitating hydrometeors, that is, heterogeneous wake‐induced nucleation (Prabhakaran et al, 2020). The experimental investigation by Prabhakaran et al (2017) of falling drops (diameter of scriptOfalse(1false) mm) in near critical point conditions of pressurized sulfur hexafluoride showed the evidences of homogeneous nucleation in the wake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical processes contributing to the production of secondary ice particles (Field et al, 2017) within a mature cloud cannot explain the observed discrepancies between the measured activation and the observed hydrometeor population, which is several orders of magnitude higher than expected (Huang et al, 2017;Pruppacher & Klett, 2010). One possible explanation of this riddle might be the wake-induced supersaturation (Chouippe et al, 2019;Fukuta & Lee, 1986;Gagin, 1972) and activation of aerosols behind large precipitating hydrometeors, that is, heterogeneous wake-induced nucleation (Prabhakaran et al, 2020). The experimental investigation by Prabhakaran et al (2017) of falling drops (diameter of (1) mm) in near critical point conditions of pressurized sulfur hexafluoride showed the evidences of homogeneous nucleation in the wake.…”
Section: Introductionmentioning
confidence: 88%